Nutrition Status Of Children (1-6 Years) In Slums Of Ghaziabad City - Garg S.K; Singh J.V; Bhatnagar M; Chopra H (Wolters Kluwer Medknow Publications, 1997)
Research question : What are the nutritional problems of pre- school children in slums? Objectives: (i) To assess the nutritional status of the children . (ii) To find out the nutritional deficiency disorders in them (iii) To study their dietary intake. Study design: Cross- sectional. Setting : Slums of Ghaziabad city. Participants :771 children (1-6 years). Study Variables : Age, sex, caste, ICDS beneficiary status, weight, nutritional deficiency disorders, dietary intake and supplementary nutrition. Statistical analysis : Simple proportions and Chi- square test. Results : A majority (58.2 %) of children were having under nutrition of varying grades irrespective of their sex and caste but influenced by their age and ICDS beneficiary status. Anaemia, xerophthalmia and goitre were present in 14.7%, 1.6% and 0.6 % children respectively. Average daily dietary intake of energy & nutrients were lower than the recommended daily allowances (RDA). Conclusion: Regular nutritional supplementation along with adequate nutrition education would reduce the nutritional deficiency disorders among children.